Empirical market microstructure - Hasbrouck, Joel. (Oxford ; New York : Oxford University Press, 2007)
This book is a study of the trading mechanisms in financial markets: the institutions, the economic principles underlying the institutions, and stastical models for analysing the data they generate.
Introduction -- Trading mechanisms -- The roll model of trade prices -- Univariate time-series analysis -- Sequential trade models -- Order flow and the probability of informed trading -- Strategic trade models -- A generalized roll model -- Multivariate linear microstructure models -- Multiple securities and multiple prices -- Dealers and their inventories -- Limit order markets -- Depth -- Trading costs : retrospective and comparative -- Prospective trading costs and execution strategies.
Includes bibliographical references (p. 183-195) and index.
osa15/05/13
Loans
Keywords: Securities; Securities -- Prices; Investments -- Mathematical models; Stock exchanges -- Mathematical models